ANALISIS EVALUASI FORMATIF PADA MATERI PERSATUAN DAN KESATUAN BANGSA MATA PELAJARAN PKN KELAS IV DI SD BUDI MULIA CILEDUG - Ina Magdalena; Febtiya Eka Safitri; Fiki Nurul Latifah; Vivi Dian Pratiwi; Fatimatu Zahra A (STKIP Persada Khatulistiwa Sintang, 2020)
The purpose of this study was to analyze formative evaluations on the nation's unity and unity subject matter in class IV PKN subjects at SD Budi Mulia Ciledug. This research is a qualitative research with a descriptive qualitative research design. The population that researchers took in this study were all students of grade IV Budi Mulia Elementary School consisting of 2 classes with a total of 40 students. Class IVA was selected as a sample because most of the students' learning outcomes were low on PKN lessons. Data collection tools obtained from observation, interviews and documentation. The findings generated in this study that with formative evaluation can increase student learning activities on PKN subjects and can improve learning outcomes, and students become active in working on the problems given by the teacher. Part of the students already understand the material because at the end of each lesson always given formative evaluation by the teacher. The evaluation used is multiple choice because it is more effective. Formative evaluation can increase student learning activities, this can be seen from the activeness of students when learning takes place and students always collect assignments on time.